Barry Schermer: His Consumer Bankruptcy Greatest Hits - Wendell J. Sherk; Kathy A. Surratt-States (Washington University Journal of Law & Policy, 2017)
This Article reflects on major decisions given by Judge Barry Schermer in the field of consumer bankruptcy. Sherk and Surrat-States focus on In re Copman, In re Wilmsmeyer, In re Mitchell, and In re Long, and how Judge Schermer’s decisions and influence were helpful within and beyond the Eastern District of Missouri Bankruptcy Court. The Article concludes Judger Schermer has had an important role in shaping the niche are of consumer bankruptcy law over his thirty years of tenure.
Keywords: Judge Schermer; Bankruptcy; Chapter 13 Bankruptcy; Bankruptcy Code; Litigation; Secured Creditors; Bankruptcy Abuse and Consumer Protection Act; Consumer Bankruptcy; Student Loan Debt; Bankruptcy Appellate Panel